2020
DOI: 10.1037/str0000137
|View full text |Cite
|
Sign up to set email alerts
|

Integrating wearables in stress management interventions: Promising evidence from a randomized trial.

Abstract: Although workplace stress management interventions have been shown to be effective, they are limited by how and when they deliver, contextualize, and reinforce content. In the current article, we evaluate whether a wearable-based stress management intervention can improve mental health outcomes. Employees (N = 169) drawn from a large technology corporation were randomly assigned to either a wearable-based treatment or waitlist control. The treatment consisted of a very brief mindfulness-based training accompan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 55 publications
0
66
0
1
Order By: Relevance
“…Four studies [ 13 , 14 , 24 , 27 ] were identified for inclusion in this review based on the secondary search term “anxiety”. The study by Balconi et al (2019) used wearable EEG and ECG (for subsequent HRV computation) devices, including either the Muse™ headband (InteraXon Inc., Toronto, ON, Canada) or the Lowdown Focus glasses (SmithOptics Inc., Clearfield, UT, USA) to determine the effects of mindfulness exercises on both an individual’s objective and subjective levels of stress and anxiety [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies [ 13 , 14 , 24 , 27 ] were identified for inclusion in this review based on the secondary search term “anxiety”. The study by Balconi et al (2019) used wearable EEG and ECG (for subsequent HRV computation) devices, including either the Muse™ headband (InteraXon Inc., Toronto, ON, Canada) or the Lowdown Focus glasses (SmithOptics Inc., Clearfield, UT, USA) to determine the effects of mindfulness exercises on both an individual’s objective and subjective levels of stress and anxiety [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac activity has been the predominant objectively measurable physiological parameter of anxiety in the literature; however, respiratory patterns have been reported to robustly indicate cognitive emotional stress [ 39 , 40 ]. The second article included in the present review, Smith et al (2020), attempted to measure respiratory rate and variability to compare physiological parameters with subjective scores of anxiety and stress, using the only wearable device (Spire Stone (Spire Health, Stanford, California)) available at the time that could measure these parameters unobtrusively [ 27 ]. Despite the capability of the device in measuring respiratory rate and variability, there was a lack of compliance by subjects in the experimental group (they only wore the device 52% of the study days), despite the majority of subjects having reported high tolerability for the device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reminder functions on smart-phones, apps, or smartwatches can support interventions, and allow them to be tailored to entrepreneurs' current level of recovery engagement (Eatough et al, 2016). A recent study using smart-watches to deliver and monitor a breathing intervention, for example, reported one sixth fewer stress instances among participants randomly assigned to the smart-watches group compared to the waiting list group (Smith et al, 2020). Smart-watches and associated health apps allow users to share information on their current levels of activity, physical exercise, and sleep (Pakhomov et al, 2020).…”
Section: Collect Demographic Datamentioning
confidence: 99%
“…Posttreatment improvement was significantly greater in the intervention group compared with the control group only for negative affect, consistent with findings of previous studies of healthy adults. 62,63 In addition, the observed improvement in pain-related disability was statistically significant in the adjusted analyses, providing preliminary evidence that diaphragmatic breathing interventions may reduce painrelated disability among survivors with chronic pain. Although results suggest some improvement on measures of pain intensity, depression, sleep, and HRQOL (specifically the physical functioning component), they were not statistically significant and require assessment in larger samples.…”
Section: Discussionmentioning
confidence: 73%